2009
DOI: 10.1007/s11255-008-9519-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting urethral stricture development after radical retropubic prostatectomy

Abstract: Our study showed that early healing of vesico-urethral anastomosis may allow early catheter removal and results in decreased rates of urethral stricture formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
6
0
2
Order By: Relevance
“…Our AS rate was 2.8% in patients without UL and raised to 7.9%, 23.5%, and 37.5% in patients with UL grade I, II, and III, respectively, thus pointing out a direct correlation between occurrence and grade of UL and development of AS. Similar findings were obtained by Altinova et al 17 who, like us, kept the urethral catheter until cystography demonstrated absence of UL. In their series, the AS rate was 4%, 12,5%, and 40% in patients who had the catheter for 1, 2, or 3 weeks, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Our AS rate was 2.8% in patients without UL and raised to 7.9%, 23.5%, and 37.5% in patients with UL grade I, II, and III, respectively, thus pointing out a direct correlation between occurrence and grade of UL and development of AS. Similar findings were obtained by Altinova et al 17 who, like us, kept the urethral catheter until cystography demonstrated absence of UL. In their series, the AS rate was 4%, 12,5%, and 40% in patients who had the catheter for 1, 2, or 3 weeks, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Literature analysis, in some cases with an antiquity greater than 10 years, describes an incidence that varies from 0.5 to 32 % (2, 3, 5-9, 17). VUAS etiology is not yet clear; inadequate contact mucosa - mucosa appears to be the genesis of this complication and most important risks factors related are smoke habits, radiotherapy, obesity, previous TURP, surgeon unexperienced, hematoma and urinary leak (5, 7, 9, 13).…”
Section: Discussionmentioning
confidence: 99%
“…Despite precise anatomical knowledge and technical developments in radical prostatectomy for prostate cancer, postoperative anastomosing stricture is still relatively common 2,3 . However, it can usually be managed successfully with one graduated dilatation 4 .…”
Section: Discussionmentioning
confidence: 99%